Maximum yield and survival of perennial pigeonpea (Cajanus cajan) by improving planting site, watering and chemicals - NIMBOLE, N N (The Indian Journal of Agricultural Sciences, 2013)
Performance of bushy perennial ’ICP’ 8094’ pigeonpea (Cajanus cajan (L.) Millsp.] was evaluated during 1993-95 on medium deep (50.6 cm) Altisol in semi-arid environment. The treatments comprised improvement in planting sites (micrositing), minimal watering, use of castor (Ricinus communis L.) cake and plant-protection chemicals to achieve high grain yield and plant survival. Micrositing increased the grain, lodder and fuel production several-folds compared with sowing on flat bed soil (control) in first as well as second harvest in first and second year (ratoon). The yields were higher in the ratoon crop then in the first-year crop. Supply of water improved the grain production, although not signitlcantly. Castor cake and micrositing caused lower seedling emergence initially, which improved with gap filling. The plant survival was excellent (87%) with micro siting but very poor (10%) with the control at 575 days after sowing. The highest survival and yield with micro siting may be due to the low bulk density (1.15 g/ce) and high plant-available water-holding capacity (112 mm) of the microsite-mixture pro the. However, the survival at 650 days after sowing was poor Â (15-33%) in all the treatments due to severe and repeated attack of the termites (Odontotermes sp and Microtermes sp).